Prevention of complications related to peripherally inserted central catheter insertion techniques in newborns: systematic review and network meta-analysis - Ludmylla de Oliveira Beleza; Guilherme da Costa Brasil; Amanda Salles Margatho; Christiane Inocêncio Vasques; Renata Cristina de Campos Pereira Silveira; Priscilla Roberta Silva Rocha; Laiane Medeiros Ribeiro (Universidade de São Paulo, 2024)
Objective: to analyze the effectiveness of peripherally inserted central catheter insertion techniques in preventing the occurrence of complications related to this device in newborns. Method: a paired and network systematic literature review and meta-analysis, with its search carried out in seven databases and in the Grey Literature, including randomized and non-randomized clinical trials. The risk of bias was assessed using the Cochrane Risk of Bias 2 and Risk of Bias In Non-randomized Studies of Interventions tools. Certainty of the evidence was assessed by means of the Grading of Recommendations Assessment, Development and Evaluation. A meta-analysis was carried out with the aid of the R statistical program. Results: eight studies with 1,126 newborns were included and six insertion techniques were identified: intracavitary electrocardiogram; intracavitary electrocardiogram associated with ultrasound; ultrasound; formula; anatomical landmark; and modified anatomical landmark. Five techniques significantly decreased primary tip malpositioning when compared to the control ( p <0.05). Intracavitary electrocardiogram significantly and more effectively reduced arrhythmias, general complications and phlebitis; the technique that used a formula also reduced general complications. Infection, infiltration, secondary tip malpositioning, catheter rupture, thrombosis, occlusion and catheter-associated skin lesion were not significantly preventable events. Conclusion: intracavitary electrocardiogram and use of the formula were the most effective techniques in reducing complications.